DICTIONARIES USED IN ENGLISH LITERATURE - Tamara Ibrokhimovna Qarshiyeva; Sharifa Ismailovna Nabiyeva (Western European Studies, 2025)
This article discusses the role of vocabulary and stylistic language—often referred to as “literary dictionaries” or vocabularies—in English literature. It emphasizes how word choice enhances emotional depth, imagery, and stylistic expression in literary texts. The article explores the use of metaphors, symbolism, and personification, and highlights how historical and cultural contexts have shaped literary vocabulary over time. From the Renaissance to the Victorian era, and into modern literature, authors have used language creatively to reflect characters, themes, and societal changes. It also notes the evolution of vocabulary in modern literature, influenced by technology and global culture. The article concludes by emphasizing that the vocabulary in literary works is purposefully chosen to connect deeply with readers and express complex ideas.
Keywords: English literature; literary vocabulary; stylistic devices